Anaerobic co-digestion of animal manure at different waste cooking oil concentrations - Sunada, Natalia da Silva; Amorim Orrico, Ana Carolina; Previdelli Orrico Junior, Marco Antonio; Lucas Junior, Jorge de [UNESP]; Teixeira Lopes, Walter Renato; Schwingel, Alice Watte (Univ Federal Santa Maria, 2018)
This study aimed to obtain the best dose of waste cooking oil inclusion for the co-digestion of substrates prepared with dairy cattle and swine manure in order to maximize solids reductions and biogas yield. Analyses of total solids (TS), volatile solids (VS), and neutral detergent fiber (NDF) were performed during the loading and unloading of digesters, while biogas yield was measured twice a week. The maximum reduction in VS (51.4%) was reached with the inclusion of up to 54.6 g waste cooking oil. kg manure(-1). Maximum NDF degradation occurred with inclusions of up to 69.4 g waste cooking oil.kg manure(-1). Inclusions of up to 64 g of waste cooking oil.kg manure(-1) provided specific biogas yield of 291.4 and 251.0 L biogas. kg VS added(-1) to substrates with swine and cattle manure, respectively. Adding oil at doses between 45.1 and 69.4 g waste cooking oil kg manure(-1) to substrates composed of cattle or swine manure maximizes reductions of solids and fibrous constituents and enhances specific biogas yield. Furthermore, swine manure supports higher doses of waste cooking oil.
Keywords: digestion; biogas; energy recycling